New-Onset Intracranial Hemorrhage in A Patient with Glioblastoma Multiforme: A Case Report - Adam Arya Pratama; Meritania Ridianti Putri; Hanis Setyono (Magna Neurologica, 2026)
Background: Glioblastoma multiforme (GBM) is the most common and aggressive primary brain tumor in adults. GBM is a high-grade glioma of the central nervous system associated with high morbidity and/or mortality, often accompanied by Intracranial Hemorrhage (ICH).  Case: This study reports a 62-year-old male patient presenting with sudden-onset weakness in the left extremities, which worsened over the past week, without any history of trauma. A non-contrast computed tomography (CT) scan of the head revealed the presence of ICH. Laboratory findings showed leukocytosis and mild hyponatremia. The patient had previously been diagnosed with glioblastoma in the right parietal region, confirmed through magnetic resonance imaging (MRI), which revealed multiple lesions with solid-cystic components. The patient had undergone tumor removal surgery via craniotomy for further histopathological examination. A repeat craniotomy was performed to evacuate the ICH. Following the evacuation of the hemorrhage, clinical improvement was observed. Discussion: GBM classically presents with symptoms of increased intracranial pressure and gradually progressive neurological deficits. GBM also enhances vascular endothelial growth factor (VEGF) activity, contributing to the increased incidence of ICH. Acute presentation with ICH and rapid clinical deterioration is rare. The current treatment options for GBM are multimodal, including surgical resection, radiation therapy, and chemotherapy.  Conclusion: GBM presenting with ICH is uncommon but life-threatening. This case underscores the need for high clinical suspicion and immediate neuroimaging in patients with known or suspected GBM presenting with acute neurological decline. Timely surgical intervention can improve outcomes.